Empowering Regulatory Agility: Bridging the Technological Gap for Effective Digital Markets Oversight - Anna Renata Pisarkiewicz; Pier Luigi Parcu (International Telecommunications Society (ITS), 2024)
The digital economy, which keeps transforming how people and businesses interact and operate, has certain distinctive characteristics that pose unique challenges for regulators. It is highly dynamic and driven by innovation, which in comparison to the past, happens at a much faster pace and is more disruptive. It is technology-based and, more than before, data-driven, which means that it requires notable ICT and analytic capabilities and the ability to interpret and make decisions based on vast amounts of data. For example, to understand the economies of scale in search and the value of targeted advertising, the UK CMA requested and analysed over 4TB of data from Google and Bing during its market study on digital advertising (Hunt, 2022). Moreover, the digital economy with its corresponding digital regulations is increasingly complex and interconnected, making it difficult for regulators to understand and coherently regulate specific problems or components without examining entire digital and regulatory ecosystems. The digital economy also transcends traditional sectoral silos as well as territorial and jurisdictional limitations, thereby presenting challenges in terms of ensuring harmonized regulatory frameworks and effective compliance across different national authorities and different geographical realities. The German Facebook (Meta) case and the subsequent preliminary ruling from the EU perfectly illustrate both the increasingly blurred lines between data protection and competition law enforcement as well as a need for coordination and collaboration between the respective regulators. Finally, the global and interconnected nature of the digital economy creates important dependencies and vulnerabilities that regulators must understand and navigate, which exposes regulation to geopolitical tensions. The interplay between merger control and foreign direct investment (FDI) screening, for example, in cases involving semiconductors shows how regulatory frameworks must adapt to address these dependencies and vulnerabilities, ensuring that economic considerations are balanced with national security interests amidst rising geopolitical tensions.
Keywords: 330; Regulatory agility; digital markets; enforcement; VUCA framework; collaborative regulation; technological gap; technological proficiency; innovative policymaking; competences